Islamic Architectural Heritage Properties in Iraq - Hila, Dr. Maysoon Muhi (International Journal of Scientific Research in Civil Engineering, 2016)
The concept of (architectural heritage) is more concepts interesting by The scientific community in Iraq and has long been a relatively dating its beginnings to the early sixties of the twentieth century, and coincides with the establishment of the Iraqi school of architecture in fifties, and since that time has increased awareness of the importance of architectural heritage as one of the ingredients for a sense of identity and continuity of civilization. Islamic architecture in Iraq Characterized on mosques as a field essential to reverse the manifestations , so it was a great place for social effectiveness as minarets emerged on the difference others before and there were multiple types of contracts starting from the semi-spire to full eara to half of the ring , and then appeared cornice, a trim architectural resembling beehives used in mosques in which layers are paved with two purposes ,Structural and decorative at the same time ,Column decorated with a crown is also used as a structural and decorative e marked Islamic column Brchagueth measure of Greek columns with Romania decorated with crown Neck long and sometimes busy square Page( muqarnas) or square gang Adorned with magnificent geometric decoration made, with forms that are based( Alarbisk) the characteristics of the traditional architecture of the Iraqi use of domes that many Use in mosques, shrines, it has been domes in the first Covenant and even The end of the eleventh century AD a small, confined spaces used to cover the front of the (mihrab) then spread use of shrines and hired the first command to work this angle to facilitate the transition from the box to the appraiser decades, the elements of traditional architecture concentrated as follows : Decorative elements: The plant motifs are of the most prominent manifestations Explain away the Arab-Muslim artist for simulation of nature and transfer Literally, there is almost identifies, And leaves only lines curved or curled connection with some live. Engineering elements taken geometric particularly important in Arab-Islamic architecture in general, and enjoyed a unique personality unmatched. To bring more beauty that corresponds to the presence of unlimited